Complications classification of local cold injury - M. I. Mikhailichenko; K. G. Shapovalov; V. A. Mudrov (Вестник хирургии имени И.И. Грекова)
The OBJECTIVE of this work was to develop a classification of complications of local cold injury.METHODS AND MATERIALS. The study is based on the results and analysis of the treatment of 132 patients with local cold injury of the II–IV degree of the lower extremities. The victims were hospitalized in the regional center for thermal trauma on the basis of the «City Clinical Hospital № 1» in the period from 2018 to 2019. Post-traumatic complications were detected in 54 patients (40.1 %), of which 32 developed early and 22 patients developed late complications. The remaining 78 patients after discharge from the hospital did not seek medical help again and were under the supervision of a polyclinic surgeon.RESULTS. In the course of the study, it was found that in 32 out of 132 patients in the early period of local cold injury of the lower extremities, sensitivity disorders, muscle weakness, convulsions, impaired coordination of movements, graft rejection, wound suppuration and suture failure, stump necrosis were detected in the affected segments of the extremities. 22 victims developed late complications of local cold injury: trophic ulcers of the stumps of the feet, osteomyelitis with the formation of sequesters, gangrene of the stumps of both feet. As a result of the study and pathogenetic interpretation of the consequences of cryoinjury, a new classification of complications of local cold injury was formed and the criteria for the forms of «cold extremity» were identified.CONCLUSION. Post-traumatic complications were detected in almost half of the victims with local cold injury (54 patients, 40.1 %). Thus, in the early stages of cryoinjury, 32 patients were found to have impaired sensitivity of the affected limb, muscle weakness, convulsions, and impaired coordination of movements; 4 (12.5 %) had treatment complicated by graft rejection; 5 (15.5 %) had wound suppuration and suture failure; 2 (6.25 %) had stump necrosis. In the late period, complications of local cold injury were registered in 22 patients. Of these, 12 (55 %) patients were found to have trophic disorders; osteomyelitis was detected in 8 (36 %) patients; in 2 (9 %) — gangrene of the distal segment of the affected limb.